Meat quality, meat fatty acid composition, and effects of transport stress on crossbred pigs in Malaysia - Fong, Michelle Wai Cheng (2019)
Pork meat quality and local genetic diversity of pigs is relatively unknown in Malaysia since the abolishing of designated breeder farms and centralized suppliers since the Nipah virus outbreak in Malaysia. This is compounded by the presence of unlicensed slaughterhouses, which threatens the quality of pork for the consumer. This study seeks to determine the general pork quality from model farms in Malaysia, as well as the effect of transportation duration on meat quality, stress parameters and HSP70 expression. This study also compares the Warner-Bratzler Shear Force (WBSF) values between the roasted and boiled meat to approximate local consumer preference and laboratory meat quality evaluation method. Meat quality parameters were evaluated from the longissimus dorsi of 10 Duroc crossbreeds to estimate that the local pork quality falls into the category of Red, Soft and Exudative meat (acceptable with mild defects). The fatty acid profile analysis done on the longissimus dorsi of 6 Landrace pure breed, 4 Large White pure breed and 10 Duroc crossbreds showed that the Duroc crossbreds have the lowest saturated fatty acid content and the highest unsaturated fatty acid to saturated fatty acid ratio compared to pure breeds. However, producers may need to increase the polyunsaturated fatty acid omega 3 (PUFA n-3) levels in Duroc crosses due to high PUFA n-6: n-3 ratio. As for the effects of transportation, 20 Duroc crosses were assigned to long transportation stress (3-hour transportation duration), while 10 Duroc crossbreds were subjected to short transportation stress (30-minute transportation duration). A transportation duration of 3 hours is correlated with high serum corticosterone levels, down-regulation of heat shock protein 70 (HSP70) expression, higher tendency of muscle lipid oxidation and lower pH45minutes when compared to the short transportation group. This study suggests that the initial stress caused by short transportation durations of 30 minutes up-regulates the expression of HSP70 for cellular repair mechanism. This mechanism is severely impacted after 3 hours of transportation stress, leading to the downregulation of HSP70 and the tendency of increased cellular oxidative potential in the muscle. In conclusion, the proposed pork quality baseline reference falls within the RSE category, still deemed satisfactory in terms of consumer perception with Duroc cross still demonstrating consumer preferable meat quality and fatty acid composition compared to the other breeds. Results heavily suggests keeping the transportation time limit to within 3 hours to reduce further negative impact on meat quality. These may be achieved contributing to the benefits of the establishments of pig farming areas (PFA) within the country. HSP70 gene expression may be potentially used as a biomarker for drip loss. This study also suggests a pathway where the expression of HSP70 can be associated with changes in meat quality supported by high correlations. This study presents pork quality from Malaysian model pig farms to serve as a guideline to other pork producers, as well as provides insight into how transportation duration impacts ultimate meat quality.